At War : The Military and American Culture in the Twentieth Century and Beyond (Book collections on Project MUSE., 2018)
"If you have grown up during the twenty-first century, you've grown up at war. The United States' wars in Iraq and Afghanistan, its interventions around the world, and its global military presence make war, the military, and militarism defining features of contemporary American life. The military and the wars that it fights shape all aspects of American life - from the formation of racial and gendered identities to debates over environmental and immigration policy. Warfare and the military is ubiquitous in popular culture and the question of who should serve and how they should be treated when they return is central to definitions of proper citizenship. In short, interrogating the place of the military in American culture is central to the study of U.S. history, and understanding the cultural dimensions of American militarism is essential to studying military history. At War: Militarism and U.S. Culture in the 20th Century and Beyond offers short, accessible essays by established scholars addresses the central issues in the new military history - ranging from diplomacy and the history of U.S imperialism to the environmental issues that war raises and the ways that war shapes and is shaped by discourses of race and gender to questions of who serves in the U.S. military and why and how U.S. wars have been represented in the media and in popular culture. Each chapter will place its topic in a broad historical context, beginning in the late nineteenth century and examining how the issue has evolved over the past 125 years."--Provided by publisher.